Bio-Inspired Materials for Biomedical Applications - Pollini, Mauro; Paladini, Federica (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Evolved in a huge number of different materials and structures, nature represents a great inspiration for scientists and researchers, which continuously focuses attention on the development of novel approaches and functional biomaterials to mimic the complex architectures and functions of the human body. Bioinspired engineering is considered today as a valuable tool for the design of clinically relevant materials and structures for regenerative sciences and, in this direction, many progresses have been recently made by the scientific research in the biomedical field. This book aims at collecting some recent works addressed to the definition of novel bioinspired approaches in bioengineering and biotechnology, presenting interesting scientific results and a comprehensive overview of attracting materials in research papers and review articles.